Activity And Deactivation Of Cr-Cu/modified ZSM-5 Catalyst In The Combustion Of Chlorinated VOC Pollutants In Air. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (Institut Piawaian dan Penyelidikan Perindustrian Malaysia, 2006)
The performance of chronium-copper supported over H-ZSM-5 (Si/Al=240) modified with silicon tetrachloride (Cr10Cu05/SiCl4-Z) as the catalyst in the combustion of chlorinated VOCs (Cl-VOCs) is reported.